The relationship between situational change and selectiveness in friendships for adjustment to the university. Issue 3 (2nd July 2016) - Matsushima, Rumi
Abstract : This study examined how social self-efficacy and the way friendships are maintained influenced adaptation to university life and friendship satisfaction. A questionnaire was administered to 119 female university students during July 2011 in Japan. In the first procedure, the correlation between situational change and selectiveness in friendships, social self-efficacy, university adjustment and friendship satisfaction was examined. In the second procedure, the cluster analysis was conducted to integrate situational change and selectiveness in friendships and social self-efficacy. The results showed that students who changed their attitudes based on their friends and those who selected friends based on situational change did not trust their friends, nor did they feel that they were trusted by friends. However, according to the results of the cluster analysis, students who had both characteristics of selectiveness and high social skills did not feel uncomfortable in university life.